ANALISIS PROBABILITAS GAGAL BAYAR SEBELUM DAN SAAT PANDEMI COVID-19 DENGAN MODEL MERTON PADA PERUSAHAAN LEASING TERDAFTAR DI BURSA EFEK INDONESIA - Zhafira Rory Ramadhani; Alfiana Fitri (ITB AAS INDONESIA, 2022)
The COVID-19 pandemic in Indonesia was officially announced by the government in March 2020. This study aims to determine the difference in the probability of default between before and during the COVID-19 pandemic using the Merton Model. The research approach uses a quantitative approach by testing the difference in the probability of default in leasing companies listed on the Indonesia Stock Exchange. Using descriptive statistical analysis, the sample processed in this study was obtained from a purposive sampling method of 10 companies that issue bonds and consistently issue quarterly reports (Q1-Q4) in 2019 and 2020. The Merton model is used to measure the probability of default in each research sample company.The results showed that there were differences in the probability of default before and during the COVID-19 pandemic. Calculations using the Merton Model show that in 2019 the existing leasing sector companies have a low probability of default, even almost nil, with the exception of PT Indonesia Infrastructure Finance (IIFF) and PT Mandiri Tunas Finance (TUFI). While in 2020 the ten samples experienced spike in the probability of default, the two highest being PT Astra Sedaya Finance (ASDF) and PT Mandala Multifinance, Tbk (MFIN).